2020
DOI: 10.3390/ijms21218165
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates of Transarterial Chemoembolilzation in Hepatocellular Carcinoma

Abstract: Transarterial chemoembolization (TACE) is a standard treatment for intermediate-stage hepatocellular carcinoma (HCC). In this review, we summarize recent updates on the use of TACE for HCC. TACE can be performed using two techniques; conventional TACE (cTACE) and drug-eluting beads using TACE (DEB-TACE). The anti-tumor effect of the two has been reported to be similar; however, DEB-TACE carries a higher risk of hepatic artery and biliary injuries and a relatively lower risk of post-procedural pain than cTACE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
164
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(169 citation statements)
references
References 135 publications
3
164
0
2
Order By: Relevance
“…Local interventional strategies such as transarterial arterial chemoembolization (TACE), radiofrequency ablation (RFA) and radioactive particle implantation are widely used in the treatment of advanced HCC ( Makary et al, 2020 ). The combination of TACE and RFA therapy has a synergistic cytotoxic effect on HCC and results in better local tumour control and longer survival than TACE or RFA alone ( Peng et al, 2013 ; Shimose et al, 2019 ; Chang et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Local interventional strategies such as transarterial arterial chemoembolization (TACE), radiofrequency ablation (RFA) and radioactive particle implantation are widely used in the treatment of advanced HCC ( Makary et al, 2020 ). The combination of TACE and RFA therapy has a synergistic cytotoxic effect on HCC and results in better local tumour control and longer survival than TACE or RFA alone ( Peng et al, 2013 ; Shimose et al, 2019 ; Chang et al, 2020 ; Yuan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, in the context of huge HCC in the cirrhotic liver, treatment options include liver resection, TACE, TARE and targeted therapy. [22][23][24][25] The current literature showed that in carefully selected patients with huge HCC would benefit from liver resection as upfront treatment approach. 10,[26][27][28] Likewise, several comparative studies documented the superiority of liver resection for huge HCC compared with TACE regarding overall and recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has been found to play an important role in the pathogenesis and progression of malignant tumors. As a marker of systemic inflammation, NLR is associated with cancer progression, metastasis, and prognosis in various cancers, including HCC [ 19 ]. In our study, the risk of developing postoperative recurrence increased with the rise in NLR.…”
Section: Discussionmentioning
confidence: 99%